1978
DOI: 10.1002/ijc.2910220502
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in carbohydrate moiety of human alpha‐fetoprotein

Abstract: Human AFP purified from fetal serum and amniotic fluid was separated into three different variants by chromatography on concanavalin A insolubilized on Sepharose (Con A--Sepharose). The three variants were indistinguishable in immunodiffusion and radioimmunoassay. Sera from patients with yolk-sac tumor and amniotic fluid from early pregnancy were found to contain a high proportion (15-45%) of AFP which does not bind to Con A, while AFP in fetal and newborn sera, and in amniotic fluid from late pregnancy, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…Several investigators and we have reported that the reactivity of AFP with Lens culinaris agglutinin (LCA) and concanavalin A (Con A) is a good measure for distinction between HCC, nonneoplastic diseases of the liver and carcinomas of digestive organs which metastasise to the liver (Ruoslahti et al, 1978;Breborowicz et al, 1981;Ishiguro et al, 1985;Taketa & Hirai, 1989;Aoyagi et al, 1984Aoyagi et al, , 1991. The molecular basis for the different affinity of AFP for LCA and Con A is presumed to be the difference in fucosylation at the innermost N-acetylglucosamine residue and bisectingCorrespondence: Y.…”
mentioning
confidence: 99%
“…Several investigators and we have reported that the reactivity of AFP with Lens culinaris agglutinin (LCA) and concanavalin A (Con A) is a good measure for distinction between HCC, nonneoplastic diseases of the liver and carcinomas of digestive organs which metastasise to the liver (Ruoslahti et al, 1978;Breborowicz et al, 1981;Ishiguro et al, 1985;Taketa & Hirai, 1989;Aoyagi et al, 1984Aoyagi et al, , 1991. The molecular basis for the different affinity of AFP for LCA and Con A is presumed to be the difference in fucosylation at the innermost N-acetylglucosamine residue and bisectingCorrespondence: Y.…”
mentioning
confidence: 99%
“…Dambuyant et al 13] and Ruoslahti et al [14] first demonstrated the different reac tions of hepatoma AFP and of yolk sac tumor AFP with Con A, using the technique of affinity chromatography. Within a few years the technique of Con A affinity immu noelectrophoresis became more commonly used, and thereafter LCH affinity or phyto hemagglutinin E affinity immunoelectrophoresis of AFP was an important part of the tests, not only in the diagnosis of clinical patients [1][2][3][4][5] but also in the investigation of fetal organs [10,15].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of fucosylation may be related to the rapid tumor growth [12]. An N-acetylglucosamine residue linked (31,4 to the (3-linked man nose (bisect GlcNAc) was consistently present in the sugar chain of AFP of a yolk sac tumor grown in nude mice [7,8], but AFP in sera of patients with yolk sac tumor is considered to contain a sugar chain either with or without a bisect GlcNAc since the ratio of the Con A-nonreactive subfraction was about 50% in clinical samples [11,14], fucosylated sugar chain further contains a bisect GlcNAc molecule. Since this specula tion has not yet been fully studied, the fol lowing experimental work was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…The relative abundance of lentil lectin-reactive AFP in hepatocellular carci nomas has been shown by Breborowicz et al [14], Miyazaki et al [15] and Aoyagi et al [16], The appearance of concanavalin A (Con A)-nonreactive AFP in yolk sac tumors and extrahepatic malignancies has been doc umented by several investigators [14][15][16][17][18][19].…”
Section: Molecular Species Of Afp With Respect To Lectin Affinitymentioning
confidence: 99%